Staff and patient surveillance in hospitals: Good sentinels for the emergence of new SARS-CoV-2 variants. Issue 4 (October 2022) - Khanna, Rhea; Htun, Htet Lin; Li, Anthony Lianjie; Kyaw, Win Mar; Ang, Hou; Ang, Brenda; Chow, Angela
Highlights: Enhanced measures in hospital to prevent nosocomial transmission and clusters. ARI surveillance in healthcare workers is a good sentinel surveillance for COVID-19. SARS-CoV-2 test positivity rate in ED patients reflect community COVID-19 incidence. Hospital surveillance systems complement national COVID-19 reporting systems.